Internet connectivity disruption in Uganda (Uganda) - Voidly (2026)
CRITICAL severity disruption detected in Uganda. Confidence: 65%. Data sourced from IODA.
Network Disruption Incident ID: UG-2026-0037
Keywords: internet disruption; UG; disruption; critical